1960
DOI: 10.2105/ajph.50.1.14
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chlorine in Water on Enteric Viruses. II. The Effect of Combined Chlorine on Poliomyelitis and Coxsackie Viruses

Abstract: In this study of the effect of chlorine on enteric viruses, polioviruses and Coxsackie virus in water were inactivated by combined residual chlorine.The conditions under which this happens are discussed. Differences in resistance to chlorine were found among virus strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
13
0
1

Year Published

1961
1961
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 7 publications
(1 reference statement)
2
13
0
1
Order By: Relevance
“…Using 10 mg of monochloramine/liter at pH 8, Sobsey et al reported a 4-log 10 inactivation by 104 min, which, if translated into a CT value (1,040) is similar to the 4-log 10 CT value reported here (1,100) (32). In addition, the inactivation kinetics and pH trend (monochloramine less effective at pH 8) reported by Kelly et al for CVB5 are similar to the results of the present study (21).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Using 10 mg of monochloramine/liter at pH 8, Sobsey et al reported a 4-log 10 inactivation by 104 min, which, if translated into a CT value (1,040) is similar to the 4-log 10 CT value reported here (1,100) (32). In addition, the inactivation kinetics and pH trend (monochloramine less effective at pH 8) reported by Kelly et al for CVB5 are similar to the results of the present study (21).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, relatively few studies have investigated the efficacy of monochloramine as systematically as free chlorine; frequently only one concentration, pH, or temperature has been investigated. Two notable exceptions were investigations that examined monochloramine disinfection of human adenovirus 2 (HAdV2) and coxsackievirus B5 (CVB5) at multiple pH levels (21,31).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Between oxidation reduction potential and pit a theoretical relation exists. This relationship may account for variations in inactivation velocity found as a consequence of variations in pit (3,4). In the present report the rates of oxidative inactivation ~t different values of pH are compared for different compounds.…”
mentioning
confidence: 83%
“…Among these they found concentration of residual free chlorine, virus strain, temperature and pit level. In later studies by Kelly and Sanderson (17) the inactivation by constant concentration of combined residual chlorine is investigated for non-purified virus material. The results seem in good agreement with the ones of the present work.…”
mentioning
confidence: 99%